Determination of Residual Monomer in Heat Cured of Acrylic Resin Denture Base Material after strengthening it with Titanium Nanotubes - Sahar Abdulrazzaq Naji (Journal of Global Pharma Technology, 2016)
Objectives: The objective of this introductory study was to investigate, for the first time, the impacts of incorporation of titanium nanotubes to polymethyl methacrylate (PMMA) on the remaining monomer content of the  of PMMA denture base. Methods: Forty-five specimens of heat polymerizing acrylic resin were prepared according to ISO 20795-1:2013. Divided into three groups (n=15) Methyl methacrylate was mixed with 0% (control), 2.5 weight %, and 5 weight % titanium dioxide nanotubes. TiO2 nanotubes were prepared using alkaline hydrothermal process. Gas Chromatography analyses GC-MS was used as an analytical monitoring method to quantify the remaining monomer in the cured samples. Data  were analyzed using ANOVA and Tukey's test (p < 0.05). Results: residual monomer content significantly reduced in both modified groups with TiO2 nanotubes 2.5and 5w% (0.0783,0.1407, %) respectively) compared with the unmodified group (0.1567%). Conclusion: supporting of acrylic cured acrylic denture base with TiO2 nanotubes reduces the residual monomer content significantly, which improves the physical, chemical and biological properties of the acrylic denture base material.Keywords: Acrylic resin; GC-MS; Methyl methacrylate; Residual monomer; TiO2 Nanotubes.